Pentingnya Bisnis Intelejen (BI) bagi Manajemen dalam Mengambil Keputusan untuk Kesuksesan Bisnis - Achmad Fauzi; Yulisbet Hutapea; Niyar Andina; Fika Fitriyani; Theresia Naomi Putri Manurung; Andi Ramadhan; Cahyo Rachmat Irawan; Gilang Ramadhan (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This study aims to determine the importance of Business Intelligence (BI) for management in making decisions for business success. Utilization of Business Intelligence (BI) for business success using qualitative research methods as a reference in this study. Currently, many companies use Business Intelligence (BI) systems in their management processes where the use of Business Intelligence (BI) can facilitate a comprehensive business in a relatively short time, and support better corporate decision-making. With this system, companies can benchmark company performance, see emerging market trends and improve almost every aspect of the business. The results obtained using the Business Intelligence (BI) system make a good contribution to academia, industry, organizations, and companies in making long-term business decisions for business success.